1984
DOI: 10.1200/jco.1984.2.5.414
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of low- versus high-dose medroxyprogesterone acetate in the induction treatment of postmenopausal patients with advanced breast cancer.

Abstract: In a randomized trial, 210 postmenopausal women with advanced measurable breast cancer were allocated to two different schedules of medroxyprogesterone acetate (MPA). In the induction phase they received either 1,000 mg intramuscular (IM) MPA (high dose) daily or 500 mg IM MPA (low dose) twice weekly for four weeks. The maintenance treatment consisted of 500 mg MPA IM once weekly for all patients. In total, 184 patients were considered evaluable. The response rate was significantly higher (p = 0.004) for patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Renewed interest in MPA for the treatment of advanced breast cancer was stimulated by reports of very encouraging response rates when using high doses of the drug (Pannuti et al, 1978), and subsequently a dose response curve was suggested (Cavelli et al, 1984;Tammassia et al, 1983). Retrospective correlations of serum level versus response have been used to support the concept of 'high-dose' MPA, with patients achieving serum levels in excess of 80-lOOngml-l having more chance of responding than those failing to reach these levels (Johnson et al, 1984;Schulz et al, 1984;Tammassia et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renewed interest in MPA for the treatment of advanced breast cancer was stimulated by reports of very encouraging response rates when using high doses of the drug (Pannuti et al, 1978), and subsequently a dose response curve was suggested (Cavelli et al, 1984;Tammassia et al, 1983). Retrospective correlations of serum level versus response have been used to support the concept of 'high-dose' MPA, with patients achieving serum levels in excess of 80-lOOngml-l having more chance of responding than those failing to reach these levels (Johnson et al, 1984;Schulz et al, 1984;Tammassia et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Previous pharmacokinetic studies have shown that to obtain such steady state levels may require periods of between one and 8 weeks' therapy (Schulz et al, 1984;Blossey et al, 1984). In a randomised study it has been shown that, when using intra-muscular MPA, a constant dose of 300mg weekly was significantly inferior to that same dose but preceded by one month's treatment with 1,000mg weekly (Cavelli et al, 1984). This may have been due either to a true dose response curve or to an unacceptably prolonged time taken for the low dose schedule patients to have achieved adequate serum levels and so be able to respond to the drug.…”
mentioning
confidence: 99%
“…Higher dosages seem more effective than relatively lower dosages according to some studies (3, [30][31][32]. There is no difference in efficacy between "standard" treatment with medroxyprogesterone acetate ( 1000 mg) and megestrol acetate (160 mgf taken orally each day (33).…”
Section: Progestinsmentioning
confidence: 99%
“…The need for the use of HD has been document ed by pharmacokinetic studies [4,5]. Other authors have confirmed that HD MAP can induce a percen tage of responses higher compared to low-dose re sponse [6,7], MAP antitumor activity is believed to follow two different mechanisms of action: one is a direct effect on the neoplastic cell [8], the other is an indirect action following estrogen suppression. This is a consequence of the inhibition of both the hypothalamo-pituitaryovarian axis and the hypothalamo-pituitary-adrenal axis [9], The pharmacological castration induced by MAP leads us to consider that this treatment could also be effectively used in premenopausal patients.…”
Section: Introductionmentioning
confidence: 99%